Working Memory and Its Mediating Role on the Relationship of Math Anxiety and Math Performance: A Meta-Analysis - Finell, Jonatan; Sammallahti, Ellen; Korhonen, Johan; Eklöf, Hanna; Jonsson, Bert (Frontiers in Psychology, 2022)
It has been well established that math anxiety has a negative relationship with math performance (MP). A few theories have provided explanations for this relationship. One of them, the Attentional Control Theory (ACT), suggests that anxiety can negatively impact the attentional control system and increase one's attention to threat-related stimuli. Within the ACT framework, the math anxiety (MA) – working memory (WM) relationship is argued to be critical for math performance. The present metanalyses provides insights into the mechanisms of the MA – MP relation and the mediating role of WM. Through database searches with pre-determined search strings, 1346 unique articles were identified. After excluding non-relevant studies, data from 57 studies and 150 effect sizes were used for investigating the MA – MP correlation using a random-effects model. This resulted in a mean correlation of r = -0.168. The database search of WM as a mediator for the MA – MP relation revealed 15 effects sizes leading to a descriptive rather than a generalizable statistic, with a mean indirect effect size of –0.092. Overall, the results confirm the ACT theory, WM does play a significant role in the MA – MP relationship.